Review of the Deltocephalus group of leafhoppers (Hemiptera: Cicadellidae: Deltocephalinae) in China - Zhang, Yalin; Duan, Yani (Zootaxa, 2011)
The Deltocephalus group is revised from China. Deltocephalus Burmeister includes 4 species, Recilia Edwards includes 1 species and Maiestas Distant includes 31 species, of which 12 are new and an additional 13 are newly recorded for China. The new species described are: D. uncinatus, M. crura, M. cultella, M. dinghuensis, M. irisa, M. pararemigia, M. pileiformis, M. remigia, M. rostriformis, M. scalpella, M. webbi and M. yangae spp. nov. The newly recorded species are: D. pulicaris (Fallén), D. vulgaris Dash & Viraktamath, M. bilineata (Dash & Viraktamath), M. brevicula (Dash & Viraktamath), M. heuksandoensis (Kwon & Lee), M. horvathi (Then), M. latifrons (Matsumura), M. obongsanensis (Kwon & Lee), M. samuelsoni (Knight), M. subviridis (Metcalf), M. tareni (Dash & Viraktamath), M. xanthocephala (Dash & Viraktamath) and R. coronifer (Marshall). In addition, one synonym is confirmed: M. prabha (Pruthi) is a junior synonym of M. maculata (Pruthi). The 32 species known from China are illustrated together with keys for their separation.